2002
DOI: 10.1097/00124784-200207000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Community Health Assessment in Kansas

Abstract: This article evaluates the status of community health assessment in Kansas. It describes community characteristics associated with community health assessment completion, factors contributing to success, as well as barriers and limitations that prevented Kansas communities from initiating a community health assessment or completing the process. Survey findings show that certain community characteristics such as interagency cooperation, history of success at problem solving, and shared decision-making power are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…8 Community characteristics including interagency cooperation, history of success at problem solving, and shared decision-making power were strongly associated with CHA completion, while communities with incomplete CHAs reported having less representation of community leaders in their coalitions. Communities in which a CHA was not initiated reported barriers including a lack of community interest, time, and money.…”
Section: • Community Health Assessment and Planning In Public Healthmentioning
confidence: 97%
See 3 more Smart Citations
“…8 Community characteristics including interagency cooperation, history of success at problem solving, and shared decision-making power were strongly associated with CHA completion, while communities with incomplete CHAs reported having less representation of community leaders in their coalitions. Communities in which a CHA was not initiated reported barriers including a lack of community interest, time, and money.…”
Section: • Community Health Assessment and Planning In Public Healthmentioning
confidence: 97%
“…18 The types of community stakeholders represented in CHA-CHIP activities paralleled those reported previously. 8,9,17 Most participating counties, which were predominantly rural, reported being in the early stages of the CHIP and had identified 3 community health priorities. Curtis 8 reported that 50% of the communities that completed the CHA prioritization process selected more than 3 health problems.…”
Section: Cha-chip Process and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…McFarlane and Roach (1999) suggest ongoing communication, balancing the needs of both government and non-profits, a consistent tendering process, empathy for the needs of non-profit agencies and a clear sense that both partners are committed to helping people in need. Others have identified barriers to and facilitators of collaboration or partnerships in community health (Scott & Thurston, 1997;Curtis, 2002;van Eyk & Baum, 2002). There is consensus in the literature that there is willingness for all service providers to collaborate for the purpose of addressing client needs but a lack of knowledge or training on how to do so.…”
Section: The Issuementioning
confidence: 99%